Changing Trends in Shadowing in Education for Academic Achievement in Nepal - Kshetree, Arun Kumar (Innovative Research Journal, 2024)
This paper is a part of a research conducted with the support of ’Faculty Research Grant’ from the University Grants Commission, Nepal. Different forms of shadow education used by students of high school level were studied and analysed by asking the teachers teaching in high schools and the students studying bachelor level in different universities of Nepal about their school level experiences regarding shadow education activities and the impact of shadow education in their scores. Shadow education is also called private tutoring but it covers many other ways of getting support in studies. It has been very common in Nepal and everywhere in the world since formal education started. It was a survey study based on the information gathered from the students of different faculties at the bachelor level. The research tools used included a questionnaire for the students and a set of interview guidelines for FGD and interviewing the teachers teaching in high schools of three major cities of Nepal; Butwal, Pokhara and Kathmandu. After the analysis of the information gathered, it was found that the trends of getting shadow education and related activities was drastically changed not just in the form but also in the purpose of getting shadow education. The students were found to be using different forms of shadowing in education in Nepal and the trend of shadowing has also been changing with the development and incorporation of ICTs in education and online applications. The paper also presents that the changing trends in shadowing activities have also changed the lifestyles of the teachers as well.